Experimental Study on COD and BOD Treatment of Petrochemical Wastewater Using Photocatalytic Degradation - fatemeh poladzadeh; Hamid Kazemi Esfeh; leila samiee (Journal of Petroleum Science and Technology, 2022)
TiO2 photocatalyst was used to degrade Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) from petrochemical wastewater. The photocatalytic performance of the TiO2 was studied with variations of treatment parameters such as temperature, pH, contact time, and catalyst dosage. Design of Experiment (DOE) utilizing the Taguchi method was used to find and optimize the process model. Results for photocatalytic degradation of COD and BOD indicated the proper performance of TiO2 as the photocatalyst. The best result was achieved at pH 5 after 90 min with 73% COD conversion. COD degradation of petrochemical waste was optimized according to the experimental results, while process optimization indicated best process conditions are pH ≈ 5.2, temperature ≈ 42.8 °C, catalyst dosage = 0.75, and contact time of 88 min.